PENGEMBANGAN LEARNING MANAGEMENT SYSTEM (LMS) TERINTEGRASI LITERASI AL-QUR’AN: ANALISIS KURIKULUM FISIKA UMUM DI UNIVERSITAS ADZKIA - Ilham Adi Putra; Nova Hayati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research identified opportunities to enhance the integration of Qur'anic literacy in the General Physics curriculum at Adzkia University.. The purpose of the research is to analyze the curriculum and develop a Learning Management System (LMS) that integrates Qur'anic literacy. The methodology used was qualitative with a case study approach, including analysis of curriculum documents, interviews with lecturers and students, and surveys to collect data on integration needs. The results showed that currently the integration of Qur'anic literacy in physics materials is minimal, although there is interest from lecturers and students to include religious values. The survey also indicated that an integrated LMS could improve student engagement and understanding. The proposed LMS development includes modules that link physics materials with Qur'anic references, as well as interactive features. The findings recommend curriculum revision to accommodate the integration of Qur'anic literacy and the use of an LMS to improve learning effectiveness.